Quantification of total endogenous ascorbic acid from chrysanthemum (Chrysanthemum × morifolium) cultivars and its association with postharvest life - HIREMATH, VARUN M; JAIN, RITU; JAIN, NEELU; ARORA, AJAY; SWAROOP, KISHAN; SINGH, M K; KUMAR, PRABHAT; KUMAR, GUNJEET (The Indian Journal of Agricultural Sciences, 2018)
In the present study, an effort was made to quantify the total endogenous ascorbic acid to reveal if it has any association with vase life of chrysanthemum (Chrysanthemum × morifolium Ramat) cultivars. Among 30 cultivars, maximum total ascorbic acid content (441.29 mg/100 g fresh weight) was recorded in cv. Red Gold followed by cv. Jaya (336.34 mg/100 g fresh weight) and minimum ascorbic acid content (93.55 mg/100 g fresh weight) was observed in cv. Arka Ravi followed by cv. Yellow Reflex (101.76 mg/100 g fresh weight). Chrysanthemum cultivars were found to contain maximum total ascorbic acid content in petals (235.00 mg/100 g fresh weight) and leaves (285.12 mg/100 g fresh weight) in stage II (fully opened flower). During all the stages of flower development total ascorbic acid content in leaves was recorded higher as compared to petals. It is concluded that there is a significant association between postharvest life and ascorbic acid content in leaves (r = 0.669) and petals (r = 0.547) at fully opened flower stage in chrysanthemum.